Defective protein persulfidation is involved in obesity associated skeletal muscle dysfunction: role of SIRT-1 - M. Smimmo; V. Casale; D. D'Andrea; I. Bello; N. Iaccarino; F. Romano; V. Brancaleone; E. Panza; R. d’Emmanuele di Villa Bianca; A. Katsouda; E. Mitidieri; I. Antoniadou; et al. (Redox Biology)
Ectopic fat deposition in skeletal muscle (SKM) due to obesity leads to biochemical and morphological alterations that deteriorate SKM quality and performance. Here, we show that impaired MPST-derived hydrogen sulfide (H2S) signaling contributes to obesity-related SKM dysfunction. Muscle tissues from obese db/db mice exhibit reduced MPST expression, correlating with decreased protein persulfidation and muscle performance in vivo. Mpst−/− mice show similar deficits as db/db mice, confirming the role of MPST. H2S supplementation improves locomotor activity in db/db mice and restores protein persulfidation, including SIRT-1. Myotubes placed in an ''obese environment'' display a downregulation of MPST, coupled with a reduced SIRT-1 persulfidation leading to an inflammatory state. Exogenous H2S exerts beneficial effects recovering SIRT-1 persulfidation/activity. Finally, muscle biopsies from obese individuals show reduced MPST expression, underscoring the translational relevance to human SKM health. Our study unveils a crucial role for MPST-derived H2S in obesity-associated SKM dysfunction via SIRT-1 persulfidation, highlighting the importance of the MPST/H2S pathway in maintaining healthy SKM function.